2021
DOI: 10.1128/spectrum.00871-21
|View full text |Cite
|
Sign up to set email alerts
|

Dose Optimization of Combined Linezolid and Fosfomycin against Enterococcus by Using an In Vitro Pharmacokinetic/Pharmacodynamic Model

Abstract: In this study, we found that linezolid combined with fosfomycin could kill Enterococcus in vitro and that the administered dose was significantly lower after the combination treatment, which could reduce adverse effects and the development of drug resistance. The potential mechanism of the two-drug combination against Enterococcus was revealed from a quantitative perspective, which is an important step toward dose optimization in simulated humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Another promising approach is the drug combination that has been used for several diseases including those of infection origin. Combos may act on different and/or complementary targets, allowing the use of lower drug concentrations and thus reducing toxic events (Wiwanitkit, 2012 ; Hendrickx et al ., 2017 ; Gaibani et al ., 2019 ; Ianevski et al ., 2021 ; Mao et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another promising approach is the drug combination that has been used for several diseases including those of infection origin. Combos may act on different and/or complementary targets, allowing the use of lower drug concentrations and thus reducing toxic events (Wiwanitkit, 2012 ; Hendrickx et al ., 2017 ; Gaibani et al ., 2019 ; Ianevski et al ., 2021 ; Mao et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases of infections caused by linezolid-resistant Staphylococcus spp. or Enterococcus spp., and in absence of valid alternatives, some associations have been proposed, although they are supported only by exploratory and mostly in vitro data [91,92]. The use of higher doses, to the contrary, is generally not recommended, because of safety concerns [93].…”
Section: Linezolid and Tedizolidmentioning
confidence: 99%
“…When the linezolid-fosfomycin combination was used at clinical isolates of Enterococcus, it prevented the emergence of resistant mutants in lower drug concentrations and was synergistic in a hollow fiber model; another in vitro study demonstrated a reduction in linezolid MIC when co-administered with fosfomycin, even though MICs for fosfomycin were relatively high (≥64 mg/L) [171][172][173]. The simulated fosfomycin regimen in this work, however, was higher than the levels achievable by oral administration [171]. In addition, an in vitro study showed that the fosfomycin-cefixime combination has synergistic killing properties against E. coli, even in half the MIC concentrations for each drug [174].…”
Section: The Potential Utility Of Oral Fosfomycin Against Endocarditi...mentioning
confidence: 99%